081 Acute derangement of cardiac energy metabolism and oxygenation during stress in hypertrophic cardiomyopathy—a potential mechanism for sudden cardiac death. (16th May 2012) - Dass, S; Suttie, J; Karamitsos, T; Watkins, H; Neubauer, S
Abstract : Introduction: Hypertrophic cardiomyopathy (HCM) is the commonest cause of sudden cardiac death in the young. The sarcomere mutations increase the energy cost of contraction and impaired resting energetics (phosphocreatine/adenosine triphosphate, PCr/ATP, measured by 31Phosphorus MR Spectroscopy, 31P MRS) has been shown. In addition, abnormal perfusion in HCM is an independent predictor of clinical deterioration and death. However, whether microvascular dysfunction is severe enough to result in deoxygenation has not been explored. We hypothesise: (1) Cardiac energetics are further impaired acutely during exercise in HCM, but not in normals or athletes (physiological hypertrophy); (2) This energetic abnormality contributes to diastolic impairment, is independent of the degree of hypertrophy or patchy fibrosis; (3) Tissue oxygenation during stress is impaired in HCM. Methods: 31P MRS (3T) was performed in 35 age and gender matched HCM patients, 12 athletes and 20 normal controls at rest and during 8 min of steady leg exercise lying prone with 2.5 kg weights. BOLD signal intensity change (SIÄ) and myocardial perfusion reserve index (MPRI) were measured with adenosine stress. Results: There was no difference in resting PCr/ATP between normals (2.14±0.36) and athletes (2.04±0.32, p=0.36). Resting PCr/ATP was significantly reduced in HCM (1.71±0.35, p<0.0001). During exercise there was a further reduction in PCr/ATP in HCM (1.56±0.31, p<0.05) but not in normals (2.13±0.34, p=0.98), or athletes (2.09±0.50, p=0.63). There was no correlation between cardiac mass, average wall thickness and rest or exercise energetics. Peak filling rates (PFR) were significantly reduced in HCM (rest: HCM 572±176, normal 745±138 p=0.01; exercise HCM 648±191, normal 845±160 p=0.02). There was a significant correlation between PFR and PCr/ATP at both rest (rs=0.78, p=0.001) and exercise (rs=0.54, p=0.039). There was significantly reduced BOLD SI∆ response in HCM (10±11% vs normal, 18±14% and athletes 17±10%, p<0.0001) as well as MPRI (normal: 1.8±0.6; athletes: 2.0±0.9, HCM 1.3±0.6, p=0.001). There was a weak but significant correlation between BOLD SI∆ and MPRI (R=0.27, p<0.0001) and between BOLD SI∆ and end diastolic wall thickness (R=0.24, p<0.001). MPRI (β 0.2, p<0.001) and wall thickness (β −0.2, <0.001) are independent predictors of BOLD SI∆. For β myosin heavy chain mutation cohort (n=12), there was a significant relationship between change in PCr/ATP and either BOLD SI∆ (R=0.48, p=0.05). Conclusion: During exercise, the pre-existing energetic deficit in HCM is further exacerbated, independent of hypertrophy. Additionally, oxygenation is blunted during stress. This may lead to acute derangement of energy dependent ion homeostasis during acute stress, resulting in ventricular arrhythmias. We offer a possible explanation for the high incidence of exercise related death in HCM and suggest that treatments that optimise energetics may be protective.